DNA interaction, cytotoxicity and molecular structure of cobalt complex of 4‐amino‐N‐(6‐chloropyridazin‐3‐yl)benzene sulfonamide in the presence of secondary ligand pyridine. (11th September 2019) - Pandya, Sachin B.; Patel, Urmila H.; Chaudhary, Kaushik P.; Socha, Bhavesh N.; Patel, Nikita J.; Bhatt, Bhupesh S.
Abstract : Novel cobalt complex of 4‐amino‐N‐(6‐chloropyridazin‐3‐yl)benzene sulfonamide (sulfachloropyridazine) has been synthesized and characterized by elemental analysis, FT‐IR spectroscopy and magnetic susceptibility (VSM). Cobalt complex of Sulfachloropyridazine (Co‐SCP) crystallized in monoclinic space group P21 /n with Z = 4. The structure is solved by direct method and refined to R = 0.099 for 4720 reflections with I ⩾4σ(I). The results of FT‐IR spectra suggest the binding of cobalt atom to the sulfonamide ligand which is in agreement with the crystal structure determination. In crystal structure, molecule is linked via, C‐H … π, C‐Cl … π and π … π intermolecular interactions. The computational studies like the optimization energy and root means square deviation compare with single crystal structure, frontier molecular orbital (Homo‐Lumo energy) and binding energy of the Co‐SCP has been carried out using DFT/B3LYP level of theory in gaseous phase. Hirshfeld surfaces and the 2D‐fingerprint analysis are performed to study the nature of interactions and their measurable contributions towards crystal packing. The interaction of the complex with DNA is investigated using viscosity measurement and absorption titration studies. The result shows the complex bind to DNA with intercalative mode with high DNA‐binding constant (Kb ). Also, in vivo and in vitro cytotoxic studies are performed using S. pombe cells and brine shrimp lethality bioassay. DNA‐cleavage study shows better cleaving ability of the complex. Abstract : Characterization of the complex using FTIR and Magnetic susceptibility. Determining the molecular structure of the complex by single‐crystal X‐ray crystallography. Interaction studies of the molecule by Hirshfeld surface analysis. DNA binding studies and cytotoxicity of the complex. Biological activity by molecular docking studies.